2013
DOI: 10.1371/journal.pone.0072102
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study on the Effects of Bisoprolol and Atenolol on Sympathetic Nervous Activity and Central Aortic Pressure in Patients with Essential Hypertension

Abstract: Objectiveβ-blockers (BBs) with different pharmacological properties may have heterogeneous effects on sympathetic nervous activity (SNA) and central aortic pressure (CAP), which are independent cardiovascular factors for hypertension. Hence, we analyzed the effects of bisoprolol and atenolol on SNA and CAP in hypertensive patients.MethodsThis was a prospective, randomized, controlled study in 109 never-treated hypertensive subjects randomized to bisoprolol (5 mg) or atenolol (50 mg) for 4–8 weeks. SNA, baroref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
2
19
0
3
Order By: Relevance
“…55 Other antihypertensive drug classes were concomitantly administered in 5 studies (amlodipine, 51 hydrochlorothiazide, 23,53 lisinopril, 46 and lisinopril or losartan 22 ), whereas an add-on treatment approach with prespecified or unspecified other antihypertensive drug classes was allowed in 7 cases. 18,19,24,46,[52][53][54] In 9 studies, 18,20,23,47,48,[54][55][56] 19,21,22,24,50,51,53 ; and 1 study 26 did not report information about blindness of treatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…55 Other antihypertensive drug classes were concomitantly administered in 5 studies (amlodipine, 51 hydrochlorothiazide, 23,53 lisinopril, 46 and lisinopril or losartan 22 ), whereas an add-on treatment approach with prespecified or unspecified other antihypertensive drug classes was allowed in 7 cases. 18,19,24,46,[52][53][54] In 9 studies, 18,20,23,47,48,[54][55][56] 19,21,22,24,50,51,53 ; and 1 study 26 did not report information about blindness of treatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Несмотря на то, что эффект является классовым, существуют данные исследований о различиях между отдельными ББ. Так, в рандомизированном исследо-вании у 109 пациентов с ранее не леченной АГ бисо-пролол был более эффективен, чем атенолол в отно-шении снижения центрального аортального систоли-ческого АД и индекса аугментации, нормированного на ЧСС 75 уд./мин [38].…”
Section: Combination Antihypertension Therapy: the "Underresearched" unclassified
“…The higher the PR, the more the artery stiffens, especially in hypertensive patients [8]. Zhou et al [9] have shown that arterial distensibility and compliance were significantly more improved by bisoprolol therapy than by atenolol therapy, and these effects were independent of any PR-lowering effects. Therefore, the PWV-lowering effect of bisoprolol could be due to its potent PR-lowering effect and to vasodilation caused by β2 stimulation benefiting arterial elasticity.…”
Section: β-Blockers For Pwvmentioning
confidence: 99%
“…Propranolol and atenolol were not effective in lowering wave reflection, but metoprolol led to a possible improvement, and labetalol, carvedilol, and nebivolol can reduce wave reflection [7]. Zhou et al [9] showed that bisoprolol had a better effect on central aortic pressure compared to atenolol.…”
Section: β-Blockers For Central Bpmentioning
confidence: 99%